Spectroscopic studies on copper(II)triphenylarsine oxide square planar complexes - Nascimento, Otaciro Rangel; Massabni, Antonio Carlos [UNESP] (My University, 1985)
Electronic and ESR spectra of the complexes [Cu(II)(tpaso)4][Cu(I)Cl2]2,[Cu(tpaso)4](NO3)2 and [Cu(tpaso)4](ClO. © 1985.